Serum antibodies against helicobacter pylori proteins VacA and CagA are associated with increased risk for gastric adenocarcinoma - Rudi, Jochen; Kolb, Christof; Maiwald, Matthias; Zuna, Ivan; Herbay, Axel von; Galle, Peter R.; Stremmel, Wolfgang (Digestive diseases and sciences, 1997)
Infection with Helicobacter pylori is associatedwith the development of gastric cancer. To study whetherthe infection with H. pylori strains expressing thevacuolating cytotoxin (VacA) and/or thecytotoxin-associated protein (CagA) is associated with an increasedrisk of developing gastric adenocarcinoma, sera of 90patients with gastric cancer and 90 matched controlswith cardiovascular diseases were investigated for the presence of antibodies to VacA and CagA byimmunoblot. Although no significant difference in theoverall H. pylori seropositivity was found betweencancer patients and controls, antibodies against VacA or CagA were significantly more frequent incancer patients than in control subjects. Seventyfive(97.4%) of 77 H. pylori-positive patients in the cancergroup, but only 60 (84.5%) of 71 H. pylori-positive control patients had antibodies against eitherVacA or CagA (χ2 6.63; relative risk,2.00; 95% confidence interval, 1.18-3.39; P =0.01). The presence of antibodies against VacA or CagAalone was also associated with an increased cancer risk (92.2%vs 80.3%; χ2 = 5.30; relative risk, 1.74;95% confidence interval, 1.08-2.78; P = 0.021, forVacA; and 87.0% vs 74.6%; χ2 4.90;relative risk, 1.61; 95% confidence interval, 1.06-2.45; P =0.037, for CagA). The relative risk for gastric cancerwas mainly elevated in patients under 65 years, but notin patients at or over 65 years. There is evidence that infection with VacA- or CagA-producing H.pylori strains increases the risk of developing gastriccancer, especially in younger patients.
Gesehen am 06.03.2025